STRATEGI BERTAHAN HIDUP BURUH TANI SAWIT DI KELURAHAN PASIR SIALANG KECAMATAN BANGKINANG KABUPATEN KAMPAR - Wirdatul Jannah; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conducted in Kelurahan Pasir Sialang Kecamatan Bangkinang Kabupaten Kampar. The purpose of this study was to determine how a survival strategy in the palm farm workers when the economic crisis hit the family household. This study, entitled